Angiotensin II receptor antagonist valsartan in treatment of patients with arterial hypertension and chronic kidney diseases. Hypotensive and nephroprotective efficacy - M L Maximov; O V Dralova (RUDN Journal of Medicine, 2010)
Angiotensin II receptor blockers are highly effective and safe drugs that reduce the activity of RAAS. Valsartan is a quality, efficient antihypertensive drug with good tolerability. The effectiveness of valsartan is a combination of hemodynamic, neurohumoral, and metabolic effects, providing a positive outlook and steadfast nephroprotective. Combining a good tolerability, ease of use and lack of significant side effects, valsartan can rightly be considered the drug of first choice for treating such patients.